The Visual Effects of Store's Signage Displays in Urban Landscape - Adeleh Talebzadeh; Azadeh Sharifi Nowghabi (Civil Engineering Journal, 2019)
Most conducted studies about urban development in architecture, urbanism and environmental graphics areas indicate that urban furnishing is one the effective factors of urban landscape, Graphic and environmental signs and structures have an effective role in inducing identifying and strengthening the sense of place, and man can realize the identity and existence of space unconsciously. If the environment has the right design, it will make us calm and cause prosperous creativity and positive moves that ultimately lead to progress. Providing the clarity, readability, and clear image of the environment gives the person a sense of security. The aim to have a clear picture of the environment is that one can easily recognize the components of the environment and connect them in their minds in an interconnected form. The irregularity of a series of elements that lacks aesthetic values has created visual distortion for the citizens. One of these cases is the store's signage, which leads to overcrowding due to irregularities, and completely violates the main purpose of the urban design which is creating visual comfort. The study conducted on paying attention to the importance of urban furnishing and designing store's signage and its role in urban landscape. It was a practical study with laboratory and survey method. The findings indicated that along with abundant issues of urban furnishing, paying attention to designing store signs has an important role in improving urban landscape.